(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
The exploitation of mangrove forests for economic purposes is rampant in tropical countries nowadays, particularly for shrimp farming, such as in the Lampung green belt in the front of the Java Sea. So, ensuring the sustainability of existing mangroves is the need of the hour. In view of above, this study aims to analyze the sustainability index of mangrove ecosystem management and the sustainability status of the mangrove ecosystem from the ecological, economic, social, and institutional dimensions using the Multidimensional Scaling (MDS) method through the Rapid Appraisal for Fisheries (RAPFISH) approach in East Rawajitu Sub-district, Tulang Bawang District, Lampung Province, Indonesia. The analysis revealed that mangrove ecosystem management’s sustainability index was categorized as ‘less sustainable’ (index 43.01 out of 100). Meanwhile, the social dimension (51.65) was categorized as ‘quite sustainable’, and other dimensions (ecological, economic, and institutional) were ‘less sustainable.’ Therefore, it is proposed that further development of the social dimension is a strategic way to develop the other three sustainability dimensions to achieve ecosystem sustainability as a whole in the study area. Alternative strategies that can be applied for sustainable management of mangrove ecosystems in East Rawajitu Sub-district, Tulang Bawang District are increasing coordination between stakeholders, creating formal regulations, increasing the productivity and creativity of Ikatan Istri-istri Petambak Dipasena (ISTANA), formulating an integrated mangrove ecosystem management plan program, undertaking rehabilitation efforts, increasing the role of mangrove groups, and increase the attention of researchers.